Connecting emerging perspectives on learning and complementary perspectives on language - Johnson, Steve (Journal of Academic Language and Learning, 2016)
In the past decade, the changing environment of higher education and the appearance of new pedagogical ideas have challenged more traditional approaches to learning that tend to focus on either disciplinary enculturation or the development of generic skills. There is now a need for ‘ecological’ perspectives on learning, as well as curricula and pedagogies that enable students to be authentic, to ‘break free’ and to ‘stand up to the world’ (Barnett, 2004, 2007). There is also a need for complementary perspectives on language as a principal means through which active meaning-making can occur. While dialogic perspectives can complement emerging perspectives on language, they can also be constrained by underlying structuralist conceptions of language. This paper argues that an ecological-semiotic perspective, largely influenced by Peirce’s semiotics (van Lier, 2000, 2004, 2008, 2010, 2011; Augustyn, 2012), provides a more adequate conception of language. The paper explores the ways in which this ecological-semiotic perspective on language, which views language learning as an active, open-ended process of meaning-making, or semiosis, complements an ecological perspective on learning, and suggests some implications and possibilities for academic language and learning (ALL) practice.